(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Historical lexicon – one of the important directions in linguistics. Object of research lexicon, laws of development and lexicon formation. One of the important purposes of historical lexicon is to find origin of language communication between the people which talk in that language, to investigate endured by them, formation stages, to define a taken place among rerated language. The historical lexicon takes as a basis language factors from the historical point of view. It not generalization of lexicon of a certain language, and demands deepening studying to rather extralinguistic factors, cultures, outlooks, customs and tradition of the people. Lexical fund of each language, lexical diversity it is connected with people history talking is this language, it is a fruit of stages of development and formation of these people, it is considered the being updated heritage, transferred of generations in generation.